Stroke Lateralization in Large Hemisphere Infarctions: Characteristics, Stroke-Related Complications, and Outcomes - Li, Jie; Zhang, Ping; Liu, Yingying; Chen, Wanli; Yi, Xingyang; Wang, Chun (Frontiers in Neurology, 2021)
Objectives: To assess the hemispheric differences in characteristics, stroke-related complications, and outcomes of patients with large hemisphere infarctions (LHI). Methods: We enrolled consecutive patients admitted within 24 h after the diagnosis of LHI (defined as an ischemic stroke involving more than 50% of the territory of the middle cerebral artery in computed tomography and/or magnetic resonance imaging). Univariate and multivariate analysis were performed to explore the association between lateralization and stroke-related complications and clinical outcomes. Results: A total of 314 patients with LHI were enrolled, with 171 (54.5%) having right hemispheric involvement. Right-sided patients with LHI had lower baseline National Institutes of Health Stroke Scale (NIHSS) score (18 vs. 22, p < 0.001), higher frequency of atrial fibrillation (69.0 vs. 52.4%, p = 0.003), and higher proportion of cardio-embolism (73.1 vs. 56.6%, p = 0.013) than the left. Right-sided LHI had higher incidence rates of malignant brain edema (MBE) (48.5 vs. 30.8%, p = 0.001) and a composite of cardiovascular events (29.8 vs. 17.5%, p = 0.011) during hospitalization. The incidence rate of 1-month mortality (34.5 vs. 23.8%, p = 0.036) was higher in right-sided patients with LHI, but there were no hemispheric differences in the incidence rates of 3-month mortality and unfavorable outcome (both p > 0.05). Multivariate analyses suggested right hemisphere involvement was independently associated with increased risk of MBE (adjusted OR 2.37, 95% CI 1.26–4.43, p = 0.007) and composite of cardiovascular events (adjusted OR 2.04, 95% CI 1.12–3.72, p = 0.020). However, it was not independently associated with 1-month death, 3-month mortality, and 3-month unfavorable outcome (all p > 0.05). Conclusions: Right-sided patients with LHI had higher frequency of atrial fibrillation and cardio-embolism than the left-sided patients. Right hemisphere involvement was independently associated with increased risk of MBE and composite of cardiovascular events during hospitalization, whereas stroke lateralization was not an independent predictor of mortality and unfavorable outcome in patients with LHI.